A meta-analysis of short-term outcome of laparoscopic surgery versus conventional open surgery on colorectal carcinoma. Issue 48 (December 2017) - Tong, Guojun; Zhang, Guiyang; Liu, Jian; Zheng, Zhengzhao; Chen, Yan; Cui, Enhai
Abstract: Objective: The aim of this article is to study the superiority and safety of laparoscopic surgery for colorectal carcinoma. Summary Background Data: Laparoscopy in rectal cancer is still not recommended as the treatment of choice by National Comprehensive Cancer Network guidelines. Laparoscopic rectal surgery is more complex and technically demanding, especially for mid and low rectal cancer. Methods: A computer-based online research of retrospective or prospective studies addressing laparoscopic surgery versus conventional open surgery for colorectal carcinoma published in the last 11 years was performed in electronic database (Wangfang Database, China National Knowledge Infrastructure, Chinese Medical Current Contents, Pubmed, Medline, Ovid, Elsevier, ISI Web of Knowledge, Cohrane Database of Systematic Reviews). Selective trials were analyzed by the Review Manager 5.2 software. Results: A total of 9 clinical trials, involving a total of 4747 patients, were identified. A meta-analysis showed that operating time was not significantly different between the 2 groups [WMD = 0.46, 95% confidence interval (95% CI): −55.68 to 56.60, P  = .99], intraoperative blood loss in laparoscopic surgery group was less than conventional open surgery group (WMD = −64.66, 95% CI: −87.31 to 42.01, P  < .01); No significant difference in the number of lymph node retrieved from postoperative pathologic specimens was found between the 2 groups (WMD = −0.75, 95% CI: −1.72 to 0.23, P  = .14); Postoperative time to flatus in laparoscopic surgery group was earlier than that in open surgery significantly (WMD = −1.22, 95% CI: −1.53 to −0.91, P  < .01). The cases of postoperative complications were significantly different between the 2 groups, which showed that the cases of laparoscopic surgery group were less than those of open surgery group [odds ratio (OR) = 0.62, 95% CI: 0.52∼0.72, P  < .01]; Moreover, hospital stay of laparoscopic surgery group was shorter than that of open surgery that showed significant difference (WMD = −2.38, 95% CI:−3.30 to −1.46, P  < .01). Conclusion: Short-term outcomes of laparoscopic surgery are superior than conventional open surgery that include more safety and feasibility, and is expected to be a standardization operation method for colorectal carcinoma.